On almost periodic solutions of the differential equation x″(t)=Ax(t) in Hilbert spaces - Gaston M. N'Guerekata (International Journal of Mathematics and Mathematical Sciences)
We prove almost periodicity of solutions of the equation x″(t)=Ax(t) when the linear operator A satisfies an inequality of the form Re(Ax,x)≥0.